IMPLEMENTATION OF COMPETENCY BASED EDUCATION (CBC) IN KENYA: CHALLENGES AND OPPORTUNITIES - Paul Okeyo Ogembo (Adisam Publisher, 2024)
Given the challenges associated with the 8:4:4 system of education CBC that is skill- based has been deemed appropriate to replace it. The first cohort students of CBC are currently in grade 8-junior secondary school that has been domiciled in primary schools. However, the implementation seems to be bedeviled by multiple challenges. It is against this backdrop that this paper purposes to look at implementation of CBC in Kenya: Challenges and opportunities. Objectives of the study were: to determine the human resource challenges facing implementation of CBC; to establish the Schools’ infrastructural challenges facing the implementation of CBC; to establish the financial challenges facing the implementation of CBC and to examine the opportunities that can be explored towards realization of the success of the implementation of CBC.The study explored empirical literature and it was underpinned by Provus Educational Evaluation Model (1973).The study established that there are a multiple challenges bedeviling CBC implementation including financial constraints towards funding the students’ fees, and for establishing infrastructure. That there is acute shortage of teachers for the CBC and more so the JSS and that even the few teachers employed requires continuous support through professional training and develop to make them competent enough towards effectiveness in the delivery. That there are serious gaps in infrastructure including science and computer laboratories and that there are opportunities available to improve on CBC delivery-including improvement on funding; hiring more teachers and giving them continuous professional development amongst others.